The Surakarta City Tourism Development Policy is based on Regional Regulation Number 5 of 2017 Concerning the Implementation of Tourism Businesses - Matius Pangeran Probo S; Vicki Dwi Purnomo; Benedictus Hestu Cipto Handoyo; Syukron Abdul Kadir (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
A city with a cultural identity (tourism) which becomes a collective spirit so that it is able to move the pulse of trade, services and education. This scheme was realized through the commitment to the birth of Surakarta City Regional Regulation (Perda) Number 5 of 2017 concerning the Implementation of Tourism Businesses. The regional regulation strengthens Surakarta City as a city with a cultural and tourism identity with various potentials. With a variety of good capital history, destinations, agro to spirituality that can be an attraction for tourists. Various agendas to encourage and make tourism a joint effort to promote regional potential are carried out at the same time that tourism is expected to have a broad economic impact. Preliminary findings in several studies show that tourism agendas managed on the basis of inter-regional partnerships have become policy nodes between local governments, one of which is in the form of Regional Regulations (Perda).